Psychometric properties of measurement tools of active aging: A systematic review. (January 2023) - Han, Shuyu; Zhou, Jia; Ji, Mengmeng; Zhang, Yizhu; Li, Ke; Chai, Xinru; Guo, Jinzheng; Gao, Shuai; Wang, Zhiwen
Abstract: Background: Active aging has become a global goal under the current aging situation. Accurate and reproducible assessment tools are prerequisites to robust and reliable results for prevalence evaluation, associated factor exploration, and intervention effect assessment. However, there remains no systematic review to summarize all active aging assessment tools and report their psychometric properties. Objective: To identify and assess the psychometric properties of patient-reported outcome measures of active aging in older adults. Design: Systematic review of measurement properties using the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) methodology. Methods: Eight databases (PubMed, EMBASE, CINAHL, Web of Science, Cochrane library, ProQuest Dissertations and Theses, CNKI, and Wanfang) were searched from January 2002 to February 2022. Studies that aim to validate patient-reported outcome measures of active aging in older adults aged 60 and over and report one or more psychometric properties were eligible for this systematic review. Methodological quality was assessed using the COSMIN Risk of Bias Checklist. We used the COSMIN criteria to summarize and rate the psychometric properties of each patient-reported outcome measure. A modified Grading, Recommendations, Assessment, Development, and Evaluation system was used to assess the certainty of evidence. Results: Twenty studies reported on the psychometric properties of 18 identified patient-reported outcome measures. Of the 20 included studies, seven explored more than five psychometric properties. Limited information was retrieved on cross-cultural validity/measurement invariance, reliability, criterion validity, hypothesis testing for construct validity, measurement error, and responsiveness. High-quality evidence on psychometric properties was provided for the Active Aging Scale and individual-level Active Aging Index. Conclusions: The findings from the included studies highlighted that the Active Aging Scale and individual-level Active Aging Index are strongly recommended to evaluate active aging in research and clinics based on the specific aims of assessment and the response burden for participants. Future studies should also develop or translate more active aging individual-level assessment tools and pay attention to the evaluation of psychometric properties. Registration: PROSPERO (CRD42021287395).